Mammalian actin‐binding protein 1/HIP‐55 is essential for the scission of clathrin‐coated pits by regulating dynamin‐actin interaction. Issue 6 (17th February 2015) - He, Kangmin; Xing, Rui; Yan, Xiaohua; Tian, Aiju; Zhang, Mingliang; Yuan, Jinghe; Lv, Zhizhen; Fang, Xiaohong; Li, Zijian; Zhang, Youyi
ABSTRACT: Actin and dynamin work cooperatively to drive the invagination and scission of clathrin‐coated pits (CCPs). However, little is known about the mechanism that orchestrates the spatiotemporal recruitment of dynamin and actin. Here, we have identified the mammalian actin‐binding protein 1 (mAbp1; also called HIP‐55 or SH3P7), which could bind to clathrin, actin, as well as dynamin, as an adaptor that links the dynamic recruitment of dynamin and actin for the scission of CCPs. Live‐cell imaging reveals that mAbp1 is specifically recruited at a late stage of the long‐lived CCPs. mAbp1 knockdown impaired CCP scission by reducing dynamin recruitment at the plasma membrane. However, actin disruption remarkably eliminates mAbp1 recruitment and thus dynamin recruitment. These data suggest that by binding to both clathrin and F‐actin, mAbp1 is specifically recruited at a late stage of CCP formation, which subsequently recruits dynamin to CCPs. He, K., Xing, R., Yan, X., Tian, A., Zhang, M., Yuan, J., Lv, Z., Fang, X., Li, Z., and Zhang, Y.—Mammalian actin‐binding protein 1/HIP‐55 is essential for the scission of clathrin‐coated pits by regulating dynamin‐actin interaction. FASEB J. 29, 2495‐2503 (2015). www.fasebj.org